Correction: Foxes, deer, and hedgehogs: The recall of focus alternatives in Vietnamese. Issue 1 (29th January 2021) - Tjuka, Annika; Nguyen, Huong Thi Thu; Spalek, Katharina
This article details a correction to the article: Tjuka, A., Nguyen, H. T. T., & Spalek, K. (2020 ). Foxes, deer, and hedgehogs: The recall of focus alternatives in Vietnamese. Laboratory Phonology: Journal of the Association for Laboratory Phonology, 11(1), 16. DOI:http://doi.org/10.5334/labphon.253 .